The role of de novo variants in formation of human anorectal malformations - Dworschak, Gabriel C.; van Rooij, Iris A.L.M.; Reutter, Heiko Martin (Genes, 2021)
Anorectal malformations (ARM) represent a rare birth defect of the hindgut that occur in approximately 1 in 3000 live births. Around 60% of ARM occur with associated anomalies including defined genetic syndromes and associations with chromosomal aberrations. The etiology of ARM is heterogeneous, with the individual environmental or genetic risk factors remaining unknown for the majority of cases. The occurrence of familial ARM and previous epidemiologic analysis suggest autosomal dominant inheritance in a substantial subset of ARM patients. The implicated mortality and reduced fecundity in patients with ARM would lead to allele loss. However, mutational de novo events among the affected individuals could compensate for the evolutionary pressure. With the implementation of exome sequencing, array-based molecular karyotyping and family-based rare variant analyses, the technologies are available to identify the respective factors. This review discusses the identification of disease-causing variants among individuals with ARM. It highlights the role of mutational de novo events.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Anorectal malformation (ARM); Birth defect; Copy number variation (CNV); De novo; Fecundity; Heritability